The Influence of Fiber Length and Concentration on the Physical Properties of Wheat Husk Fibers Rubber Composites - Maged S. Sobhy; M. T. Tammam (International Journal of Polymer Science)
Ethylene-propylene-diene terpolymer (EPDM)/wheat husk fibers (WHFs) composites were prepared using a laboratory size two-roll mill. Cure characteristics and some physical properties such as swelling, mechanical, and thermal properties of the vulcanizates were studied. The adhesion status between the WHF and rubber matrix is lacked in general, but it started to reinforce the matrix at higher WHF contents where a higher restriction to molecular motion of the macromolecules with uniformed stress distribution of the fibers is produced. From the TGA analysis, a thermally stable property is exhibited, which in turn partially enhanced the reinforcement of the WHF-EPDM composites due to the natural adhesion during vulcanization.